Stochastic analysis of seismic ground response for site classification methods verification. Issue 111 (August 2018) - Ciancimino, A.; Foti, S.; Lanzo, G.
Abstract: A database of numerical ground response analyses has been generated to assess the effectiveness of site classification schemes adopted in seismic building codes. 1-D Ground models have been generated with a stochastic approach based on a Monte Carlo procedure and the corresponding seismic response has been evaluated by the equivalent linear elastic approach for a set of natural strong motion records. The study is intended to contribute to the discussion of optimal subsoil classification schemes in terms of inter-class dispersion and reliability of the predicted amplification factors. Moreover some specific analyses have been performed to show the relevance of stiff layer inclusions and of nonlinear soil behavior on the performances of classification schemes. The variability observed for each class in the different systems indicates that simple classification schemes should be preferred according to Occam's razor statement. Highlights: A stochastic database is generated to evaluate subsoil classification schemes. Amplification factors are computed for different subsoil classes. The complexity of the multi-parameter classification schemes appears not fully justified. The influence of PI in ground seismic response should be recognized. Profiles with VS inversion have not to be excluded from the classification.